Interpenetrasi Agama Kristen dan Agama Suku dalam Tradisi Cuci Negeri di Hukurila - Agustinus Oktovianus Lopuhaa (Institut Teknologi Sepuluh Nopember, 2019)
This study aims to describe the interpenetration process between Christianity and Tribal religion in the Cuci Negeri ritual in Hukurila. The description is based on a strong dialectical process between belief systems to look for forms and give each other values in community rituals. The belief system and public narratives in interpreting this ritual are living texts, which make this study use hermeneutic analysis. From the hermeneutic analysis of the text, the Cuci Negeri ritual that experiences an interpenetration process has given birth to new values in the Hukurila community. The new value then becomes a shared value in the belief system of the Hukurila community.interpenetrasi; agama Kristen; adat; cuci negeri; cuci hati; Hukurila.